2015
DOI: 10.1111/oik.02033
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of tree genotypic diversity and species diversity effects on different guilds of insect herbivores

Abstract: Although the effects of plant diversity on herbivores are contingent upon herbivore traits and the source of plant diversity (e.g. intra‐ and interspecific), most studies have analyzed these effects separately. We compared the effects of genotypic diversity of big‐leaf mahogany Swietenia macrophylla with that of tree species diversity on two specialist caterpillars (Hypsipyla grandella stem borers and Phyllocnistis meliacella leaf miners) and three generalist leafhoppers (Cicadellidae) feeding on mahogany in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
83
5
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(98 citation statements)
references
References 48 publications
8
83
5
2
Order By: Relevance
“…For example, in a meta-analysis, Jactel and Brockerhoff [33] found that increased tree diversity reduced herbivory by specialist species, whereas the response of generalist herbivores was variable. These predictions are supported by recent studies in both tropical [9 ] and temperate [31 ] forest systems.…”
Section: Herbivore Traitssupporting
confidence: 81%
See 2 more Smart Citations
“…For example, in a meta-analysis, Jactel and Brockerhoff [33] found that increased tree diversity reduced herbivory by specialist species, whereas the response of generalist herbivores was variable. These predictions are supported by recent studies in both tropical [9 ] and temperate [31 ] forest systems.…”
Section: Herbivore Traitssupporting
confidence: 81%
“…For example, in a meta-analysis, Jactel and Brockerhoff [33] found that increased tree diversity reduced herbivory by specialist species, whereas the response of generalist herbivores was variable. These predictions are supported by recent studies in both tropical [9 ] and temperate [31 ] forest systems.Other traits such as herbivore mobility [13,34,35] and feeding mode [36] are also thought to be important predictors of plant diversity effects on herbivores but have received comparatively less attention. In an insightful review, Bommarco and Banks [35] reported that highly mobile herbivores responded more strongly to plant diversity than sedentary herbivores because they can disperse more readily and choose among plant patches of varying diversity.…”
supporting
confidence: 81%
See 1 more Smart Citation
“…, Abdala‐Roberts et al . ), and overall effects of SD and GD on plant growth across all tree species were possibly also weak due to limited interactions between widely spaced tree saplings early in the establishment of this experiment. Biomass‐mediated effects of diversity on herbivore abundance in this system may emerge as plant–plant interactions become stronger.…”
Section: Discussionmentioning
confidence: 89%
“…Levels of leaf damage were already in a range that can substantially reduce tree growth if occurring chronically over several years [48], but lower than in most related studies (e.g. [18,2022,49]), likely because the data collection was carried out relatively early in the season. Nevertheless, by studying herbivory on congeneric native and exotic tree species simultaneously, our results contribute to the lively debate on the direction of the tree diversity-herbivory relationship (e.g.…”
Section: Discussionmentioning
confidence: 99%